Transcendence: An Exploration of Collage as a Voice for Non-Binary Identity - Baldwin, Ezra Michael (Auckland University of Technology, 2023)
This practice-led, artistic inquiry considers the potential of queer collage as a visual communication device for expressing the identity and perspectives of a non-binary person navigating a world of gender conformity. The study is framed as an autoethnographic inquiry that employs heuristic methods to explore collage as a process of building and unbuilding. This process is actualised by reflective self-dialogue, iterative practice, and reflection on external feedback. The thesis contributes to emerging discourses and artistic practices related to contemporary non-binary gender identity and expression.
Keywords: Gender; Non-Binary; Queer Collage; Queer Lens; Transgender